2003
DOI: 10.1046/j.1443-9573.2003.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year follow‐up study after Helicobacter pylori eradication: Reinfection and peptic ulcer status

Abstract: OBJECTIVE:  To investigate the prevalence of peptic ulcers and Helicobactor pylori reinfection 5 years after H. pylori eradication. METHODS:  One thousand and six adults were randomly sampled from the general population in a high‐incidence region of gastric cancer. Of these, 552 subjects were confirmed to be H. pylori‐positive by using both the rapid urease test and the Warthin−Starry stain. All H. pylori‐positive subjects were randomly divided into two groups: (i) the eradication group, who received 1 week of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…3 for the developed countries [4,6,7,[10][11][12][13], and in Fig. 4 for the developing countries [16,17,19,20]. The nested meta-analysis revealed an annual recurrence rate of 1.45% in the developed and 12% in the developing countries.…”
Section: Resultsmentioning
confidence: 96%
“…3 for the developed countries [4,6,7,[10][11][12][13], and in Fig. 4 for the developing countries [16,17,19,20]. The nested meta-analysis revealed an annual recurrence rate of 1.45% in the developed and 12% in the developing countries.…”
Section: Resultsmentioning
confidence: 96%
“…Most recurrent H. pylori infections were defined as recrudescence rather than reinfection. However, high recurrence rates have been reported in Asia, ranging from 4.3 to 20.7%, in countries with a high prevalence of H. pylori infection [13–15]. Although the precise mechanism of transmission is poorly understood, socioeconomic status is presumed to play an important role in H. pylori infection [16,17].…”
mentioning
confidence: 99%
“…In this review, ‘true’ re‐infection is defined as the situation where tests for H. pylori infection, which were negative for 12 months after eradication treatment, become positive again at a later stage, based on both clinical and molecular evidence previously reported (Table 1). 21–62 Although this definition is still arbitrary and distinct from the above mentioned definition based on molecular techniques, this term provides a more practical and feasible clinical and epidemiological connotation. Thus, this definition is widely recommended and used by many investigators 25, 31, 37, 47, 50 .…”
Section: Definition Of ‘True’ Re‐infection and Calculation Of The Annmentioning
confidence: 99%
“…A total of 36 studies in which annual rates of ‘true’ re‐infection can be adapted or calculated were identified 21–56 . Of these studies, two were published as a letter and one was reported in a review 24, 28, 46 .…”
Section: Worldwide Re‐infection Rates Of H Pylori After Eradication mentioning
confidence: 99%
See 1 more Smart Citation